2013
DOI: 10.1155/2013/382802
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Management in the High Cardiovascular Risk Population

Abstract: The incidence of hypertension is increasing every year. Blood pressure (BP) control is an important therapeutic goal for the slowing of progression as well as for the prevention of Cardiovascular disease. The management of hypertension in the high cardiovascular risk population remains a real challenge as the population continues to age, the incidence of diabetes increases, and more and more people survive acute myocardial infarction. We will review hypertension management in the high cardiovascular risk popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
12
0
4
Order By: Relevance
“…The existence of a relationship between complications associated to MS and cardiovascular diseases is widely known, being hypertension one of the most important risk factor for development of cardiovascular pathologies (Maraj, Makaryus, Ashkar, McFarlane, & Makaryus, ). In the present study, SBP was slightly higher in 20 weeks‐old ZFR than ZLR, in agreement to that found by other researchers; in fact, ZFR are considered as pre‐hypertensive animals at young ages and hypertensive animals since 25–30 weeks of life (Belobrajdic, Lam, Mano, Wittert, & Bird, ; Oltman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a relationship between complications associated to MS and cardiovascular diseases is widely known, being hypertension one of the most important risk factor for development of cardiovascular pathologies (Maraj, Makaryus, Ashkar, McFarlane, & Makaryus, ). In the present study, SBP was slightly higher in 20 weeks‐old ZFR than ZLR, in agreement to that found by other researchers; in fact, ZFR are considered as pre‐hypertensive animals at young ages and hypertensive animals since 25–30 weeks of life (Belobrajdic, Lam, Mano, Wittert, & Bird, ; Oltman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the impact of hypertension in cardiovascular morbidity and mortality is higher than any other cardiovascular risk factors, including obesity, dyslipidemia, inflammation and hypercoagulable state, etc. (Maraj et al, 2013). For patients in the age range of 40-90 years, each 20/10 mmHg rise in BP doubles the risk of fatal coronary events (Ismail and Makaryus, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Candida akan menimbulkan infeksi bila berkoloni, menginvasi dan bermultiplikasi. 10,21,22 Tahap adhesi merupakan interaksi antara Candida dengan host yang merupakan syarat terjadinya kolonisasi dan invasi. Adhesin merupakan molekul pada permukaan candida yang memfasilitasi adhesi ke permukaan host, meliputi protein ALS (Agglutinin-like sequence), HWP1 (hyphal wall protein).…”
Section: Pembahasanunclassified
“…25 Banyak obat antijamur tersedia untuk pengobatan kandidiasis oral, meliputi poliene seperti nistatin, amfoterisin B serta azol seperti ketokonazol (imidazol) dan flukonazol (triazol). 21,26 Nistatin merupakan macrolide poliene aktifmembran yang dihasilkan oleh Streptomyces noursei, memiliki aktivitas fungisida terhadap C. albicans spp. Nistatin tidak diabsorbsi pada saluran gastrointestinal ketika diberikan secara oral, penggunaan nistatin secara topikal merupakan rute pemberian yang paling umum dalam kedokteran gigi.…”
Section: Pembahasanunclassified
See 1 more Smart Citation